Development of Problem Based Learning-Based Student Worksheets to Improve 4C Skills in Science Learning in Elementary Schools - Laura Lailatul Qodri; Yeni Erita; Leni Zahara; Rayendra Rayendra (Jurnal Penelitian Pendidikan IPA, 2026)
Education in the 21st century requires a shift toward student-centered learning and the strengthening of 4C skills (Creativity, Critical Thinking, Collaboration, and Communication) as mandated by the Pancasila Student Profile and the Merdeka Curriculum. Needs analysis in elementary schools shows that existing LKPD are still traditional, lack problem-solving components, do not facilitate collaboration, and have not supported higher-order thinking. This condition indicates the urgency of developing contextual and interactive LKPD based on Problem-Based Learning (PBL) to reinforce students’ 4C skills in grade IV IPAS lessons. This study aims to develop PBL-based LKPD to improve students’ 4C skills using the ADDIE model. The research was conducted in SDN 02 Maek, SDN 06 Maek, and SDN 07 Maek involving 30 students and 3 teachers. The product’s validity met the required standards, with media validation at 71.6% (valid), language validation at 80% (valid), and content validation at 66% (valid). Practicality testing showed scores of 86.3% from teachers (very practical) and 82.6% from students (very practical). The LKPD’s effectiveness was demonstrated through an average N-Gain of 0.77 (high). Thus, the developed LKPD is categorized as valid, very practical, and effective in strengthening 4C skills in grade IV IPAS learning.